My very big little world : a SugarLoaf book - Reynolds, Peter H. (Peter Hamilton), 1961- (Atheneum Books for Young Readers, 2006)
SugarLoaf, named by her baker father and dentist mother, tells us about her family, her neighborhood, and what she likes to do.